Autism spectrum disorder: The importance of genetic counseling (Research, Society and Development, 2024)
The present research is a study on the importance of genetic counseling in autism spectrum disorder (ASD). This research aims to analyze the characteristics of ASD to provide appropriate family genetic counseling. The methodology consists of an integrative literature review, which presents a summary of the subject being theoretically developed to offer better understanding and elucidation, providing an analysis of knowledge already built in previous research, that is, a synthesis of information on previously published works on the subject, and from these works expanding to new understandings of the proposed theme. All information is taken from recently published scientific articles and updated and well-documented content. In this study, we looked at the importance of genetic counseling in patients with autism spectrum disorder. Recent studies reveal that in ASD, the genetic contribution is estimated to be around 97%, with heritability accounting for approximately 81%, once again suggesting that the genetic risk is dominant. Fragile X Syndrome, caused by a mutation in the FMR1 gene, has been associated with a higher predisposition to ASD, reinforcing the need for genetic evaluations in children suspected of having autism. After a thorough literature review, it is clear that ASD is a syndrome that is difficult to elucidate. There is no specific biomarker, but numerous genetic factors with biological aspects can trigger the disorder.